The Use of Information Technology in Improving the Tiktokshop Online Business - Wina Andriyani; Abdul Muizz Wadud (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
This research was conducted to find out the benefits of information technology in improving online business in TikTok. In the corporate world, information technology has developed rapidly. This company uses information technology to increase the growth of the company itself. Looking at the current information technology has been used by various fields, including in the economic field. As we know that currently, TikTok is one of the applications that is frequently visited by the public, in 2022 the number of TikTok visitors will reach 62.52% or 1.46 billion visitors, this figure has increased compared to last year. With advances in technology, nowadays many people make purchases, one of which is through the tiktok application. Tiktok is not just for entertainment, but now Tiktok has launched the Tiktokshop feature. The research method used in this study is a qualitative method with literature study data collection techniques, so that data can be obtained through related journals, books, or other reference materials. Tiktok is one of the e-commerce platforms in Indonesia which has become a business opportunity by developing into a popular digital marketing tool. Through tiktok, someone can sell the desired item by using various digital marketing strategies. The marketing strategy commonly used in TikTok is through advertising and video content.